Finite element analysis with seismic response on RC-building’s simplified modelling - Lim Kim Chuan (2022)
Most of the reinforced concrete buildings in Malaysia are designed and built without seismic design as Malaysia is located far from the active plate boundaries until Ranau earthquake in 2015. Malaysia government had released Malaysia National Annex to Eurocode 8 in 2017 and the buildings should be designed and built according to the specification stated in this annex. The lack of attention and seismic design in reinforced concrete building as well as limited information and design performance of reinforced concrete building become the challenges in implementing seismic design and investigating the capability of Malaysian buildings toward seismic load. This paper aims to evaluate damage analysis and the location of potential weakness in the reinforced concrete buildings under different seismic intensities (0.05g, 0.10g, 0.15g and 0.20g) and reactions through SAP2000. Finite Element Model of four storey reinforced concrete buildings in Ranau, Sabah was modelled in analysing the earthquake damage to the building through pushover analysis and time history analysis with different PGA. The results show that the initial design of the concrete column is insufficient in providing the reinforcement and retrofitting is recommended for the safety of structure. All the hinges form within life safety (LS) level and the seismic performance of the modelling building is considered safe as the plastic connector is below immediate occupancy (IO) level.